2013
DOI: 10.1007/s00296-013-2787-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of isotonic and isometric hand exercises on pain, hand functions, dexterity and quality of life in women with rheumatoid arthritis

Abstract: The primary objective of our study was to evaluate the effect of 6-week-long isotonic and isometric hand exercises on pain, hand functions, dexterity and quality of life in women diagnosed as rheumatoid arthritis (RA). Our secondary objective was to assess the changes in handgrip strength and disease activity. This randomized, parallel, single-blinded 6-week intervention study enrolled 52 female patients between 40 and 70 years of age, who were diagnosed with RA according to American College of Rheumatology cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 21 publications
1
17
1
3
Order By: Relevance
“…Stucki et al [17] found that in patients with RA quadriceps muscle strength explained 12% of the variance in the self-reported activities of daily life, and women with RA were reported to have 20% lower quadriceps strength than the controls [18]. Isotonic and isometric hand exercise in RA patients can decrease pain and disease activity and increase muscle strength and function as well as quality of life [19]. Hand grip strength was shown to discriminate between various disease states of RA and seems to return to near-normative level when the disease is in remission [20].…”
Section: Introductionmentioning
confidence: 99%
“…Stucki et al [17] found that in patients with RA quadriceps muscle strength explained 12% of the variance in the self-reported activities of daily life, and women with RA were reported to have 20% lower quadriceps strength than the controls [18]. Isotonic and isometric hand exercise in RA patients can decrease pain and disease activity and increase muscle strength and function as well as quality of life [19]. Hand grip strength was shown to discriminate between various disease states of RA and seems to return to near-normative level when the disease is in remission [20].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, although osteoarthritis has a higher prevalence than rheumatoid arthritis, the studies mostly concentrated on rheumatoid arthritis. Although numerous studies investigated the effects of exercise and physical activity on disease symptoms and physical aptitude in osteoarthritis patients, there is a limited body research on determining physical activity level [20,23,24,34]. A review of the studies analyzing physical activity levels of osteoarthritis patients revealed that the patients were 40 and older [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature researchers have generally investigate the level of physical activity of the healthy population and some chronic diseases such as a cancer, obesity and cardiovascular diseases. Also large parts of the research have been designed regarding different exercise programs' effekt the symptoms of the disease in order to investigate the effectiveness of the physical activity programs [23][24][25][26][27][28][29]. To our knowledge, as yet, there is no study that investigates the physical activity levels of patients with rheumatic diseases.…”
mentioning
confidence: 99%
“…), have recently gained popularity in sports and rehabilitation settings for promotion of handgrip strength and for prevention and rehabilitation of hand-related injuries [9,10]. Previous studies that investigated the efficacy of various specialized handgrip strength training programs have been performed either in diseased individuals or in healthy untrained and physically active adults (young, middle-aged and elderly individuals), reporting either increases or no change on maximal handgrip strength [9][10][11][12][13]. However, the subjects' characteristics including age, training experience and health status are important contributing factors that could influence the efficacy of strength training program on improving indices of neuromuscular performance.…”
Section: Strength Training Induces Greater Increase In Handgrip Strenmentioning
confidence: 99%